COMPARATIVE ANALYSIS OF OBJECT-ORIENTED PROGRAMMING IN PYTHON AND JAVA - Nomozova Malika,; Muslimbek Pirnazarov, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Python and Java are two of the most popular programming languages used today, and both support Object-Oriented Programming. But anyone who has worked with both knows they feel completely different. This paper looks at how each language implements the four core OOP concepts — encapsulation, inheritance, polymorphism, and abstraction — and tries to understand why those differences exist and what they mean in practice. The comparison is based on code examples and existing literature rather than performance benchmarks. The conclusion is straightforward: neither language is better than the other. They just make different trade-offs, and knowing those trade-offs helps you pick the right tool for the right job.